Geometric Analysis of Pahudu Andung (Human Motif) In Pahikung Woven Cloth from East Sumba - Uru Ana Hida; Helminda Berta Dominggus; Linda Ade Ly; Yuliana Tamu Ina Nuhamara (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
This study aims to explore and document the mathematical concepts (ethnomathematics) contained in the Pahudu Andung motif (human motif) on the Pahikung woven cloth typical of Melolo, East Sumba. Through an ethnographic approach, this study explores the cultural, historical, and technical dimensions of the motif's creation, which have been passed down through generations. Data were collected through participatory observation, documentation, and in-depth interviews with three expert weavers (tenabi) in the Umalulu region. The results show that the Pahudu Andung motif is not merely a decorative element, but rather a visual representation rich in the geometric concepts of transformation and plane shapes. Ethnomathematic analysis identified the application of the principle of bilateral symmetry (reflection) in the body structure of the motif, translation in the repetition of the